RANCANG BANGUN PROGRAM APLIKASI PENEMPATAN TENAGA KERJA OUTSOURCING - Wahyudi Yusmawi; Ilham Eka Putra; Dessy Ratna Syari (LLDIKTI Wilayah X, 2015)
PT. Andalan Mitra Prestasi (AMP) Sungai Penuh is a firm job placement services for domestic and foreign labor and outsourcing services provider. This study was motivated by the company's information systems are not optimal. Data storage is done manually, often error reporting. The objective of this study is design of the application program employment information system outsourcing. This application uses the Java programming language. The method used is the System Development Life Cycle (SDLC). Results of this study in the form of a CD program that facilitates enterprise application placement process data and provide reports quickly and timely to realize an effective and efficient system.